Morphological constraints on changing avian migration phenology. (2nd May 2017) - Møller, A. P.; Rubolini, D.; Saino, N.
Abstract: Many organisms at northern latitudes have responded to climate warming by advancing their spring phenology. Birds are known to show earlier timing of spring migration and reproduction in response to warmer springs. However, species show heterogeneous phenological responses to climate warming, with those that have not advanced or have delayed migration phenology experiencing population declines. Although some traits (such as migration distance) partly explain heterogeneity in phenological responses, the factors affecting interspecies differences in the responsiveness to climate warming have yet to be fully explored. In this comparative study, we investigate whether variation in wing aspect ratio (reflecting relative wing narrowness), an ecomorphological trait that is strongly associated with flight efficiency and migratory behaviour, affects the ability to advance timing of spring migration during 1960–2006 in a set of 80 European migratory bird species. Species with larger aspect ratio (longer and narrower wings) showed smaller advancement of timing of spring migration compared to species with smaller aspect ratio (shorter and wider wings) while controlling for phylogeny, migration distance and other life‐history traits. In turn, migration distance positively predicted aspect ratio across species. Hence, species that are better adapted to migration appear to be more constrained in responding phenologically to rapid climate warming by advancing timing of spring migration. Our findings corroborate the idea that aspect ratio is a major evolutionary correlate of migration, and suggest that selection for energetically efficient flights, as reflected by high aspect ratio, may hinder phenotypically plastic/microevolutionary adjustments of migration phenology to ongoing climatic changes.